Organic cyclisations of propargyl and allyl bromoesters in microemulsions catalyzed by electrogenerated Nickel(I) tetramethylcyclam - Esteves, Ana Paula (2008)
While the reductive intramolecular cyclisation of propargyl and allyl bromoesters catalysed by [Ni(tmc)]+ gives good yields of the desired products using N,N-dimethylformamide as the solvent, the use of this aprotic solvent presents practical, safety and environmental issues. This paper therefore reports the search for non-toxic alternatives, in particular the study of microemulsions prepared from water, hydrocarbons, surfactant and alcohol co-surfactant. It is shown that the [Ni(tmc)]2+/[Ni(tmc)]+ couple is reversible in such media and that [Ni(tmc)]+ reacts rapidly with propargyl and allyl bromoesters to give excellent yields of cyclic products. Indeed, these microemulsions are convenient media for such syntheses.